Diagnosing human African trypanosomiasis in Angola using a card agglutination test: observational study of active and passive case finding strategies. Issue 7556 (15th June 2006) - Inojosa, Walter O; Augusto, Inacio; Bisoffi, Zeno; Josenado, Teofile; Abel, Paulo M; Stich, August; Whitty, Christopher J M
Abstract: Objective To assess the operational feasibility of detecting human African trypanosomiasis by active and passive case finding using the card agglutination test with serial dilution of serum to guide treatment. Setting Trypanosomiasis control programme in the Negage focus, northern Angola, during a period of civil war. Design Observational study. Participants 359 patients presenting themselves to health centres with symptoms (passive case finding) and 14 446 people actively screened in villages. Main outcome measures Whole blood and serological tests at different dilutions using the card agglutination test, and detection of parasites by microscopy. Results Active case finding identified 251 people with a positive card agglutination test result, 10 of whom had confirmed parasites. In those presenting for investigation 34 of 51 with a positive card agglutination test result at the dilution of 1:8 or more used to guide treatment had parasites in blood, lymph node fluid, or cerebrospinal fluid, compared with 10 of 76 in those detected by active case finding: positive predictive values of 67% for passive case detection and 13% for active case detection. Only at a cut-off dilution more than 1:32 was the positive predictive value in active case detection reasonable (46%) and at this dilution 40% of microscopically proved cases were missed. Conclusions The card agglutination test is useful for initial screening in active detection of cases with human African trypanosomiasis but, given the toxicity of the drugs, serology using the card agglutination test should be not used alone to guide treatment after active case finding. A second confirmatory test is needed.